Próteses obturadoras imediatas pós-maxilectomia: uma revisão narrativa da literatura - Silva, Francisco Lucas Inácio da (2022)
Tumor or infectious lesions in the maxilla are commonly treated with resections, which may lead to oral-nasal or oroantral communications. The maxillectomy may generate functional, aesthetic and facial damage, including difficulty breathing, chewing, swallowing, collapse of facial structures, incomprehensible speech, facial asymmetry, weight loss, and socialization difficulties. The use of a trans-surgical palatal obturator prosthesis acts through the obliteration of the surgical defect that has just arisen from the removal of the lesion, restoring stomatognathic functions. Thus, the objective of this study was to carry out a literature review in order to analyze the main advantages of installing immediate post-maxillectomy palatal obturator prostheses in patients with malignant neoplasms in the palate. Therefore, a search was carried out in the Pubmed/Medline, BVS and in the CAPES Periodicals databases, using the words in portuguese “Neoplasias Orais”, “Obturadores Palatinos” and “Prótese parcial imediata” as descriptors, as well as the English terms: “Neoplasms Mouth”, “Palatal Obturators” and “Immediate Partial Denture” combined two by two, applying the Boolean operator and with filters for the period from 2017 to 2022. Thus, a final of 26 articles were found and read in full. Studies have shown that, in the face of surgical resections in the maxilla, the installation of obturator prostheses by the multidisciplinary medical team offers advantages in the functional and psychological rehabilitation of the patient, with an immediate gain in quality of life in the immediate postoperative period. Thereby, it is essential to produce more studies on this subject by dental surgeons, aiming at improving the care of maxillectomized patients and to guarantee a postoperative period with nutritional, functional, phonetic, aesthetic and comfort advantages.